Design of Corn Kernel Separator Machine for Animal Feed - Sheila Tobing; Jordy Salim; Chendrasari Wahyu Oktavia (Institute for Research and Community Services, 2020)
The corn kernel separator machine discussed in this paper is designed for our partner, a cow breeder in Cisarua, Bogor. Our partner currently has a corn kernel separator that can work at a capacity of 50 kg per hour, but the results of the separation of kernels by the machine are not clean and the open design of the separator makes the corn kernels difficult to collect. Besides, it is challenging to find replacement parts in case of a machine failure. Our partner needs a new corn kernel separator to meet the growing need for feed as the number of cows increases. The purpose of this project is to design and build a corn kernel separator that can meet the need for animal feed at the partner’s farm. The stages of the design conducted are as follows. It begins with identifying the problems to be solved, followed by the concept design and determination of variants, the implementation of the best variant, and the detailed design including calculations needed before fabrication. The result of the design process is the realization of a corn kernel separator machine with an average capacity of a minimum of 138 kg per hour that meets the requirement of the partner. Besides, with this new corn kernel separator, the results of the separation are neater and the corn kernels are not thrown out of the machine during the separation process. The machine uses a shaft with a combination of pins and chains to separate the kernels and is driven by a 1-phase electric motor.